Addressing “what matters most” to reduce mental health stigma in primary healthcare settings: a qualitative study in Lebanon - Racha Abi Hana; Eva Heim; Pim Cuijpers; Marit Sijbrandij; Rabih El Chammay; Brandon A. Kohrt (BMC Primary Care)
Abstract Background “What matters most” (WMM) is a theoretical framework based on medical anthropology and draws on cultural concepts of values and morals. It has been employed to identify cross-cultural aspects of mental health stigma. This approach assists practitioners, advocates, and researchers in assessing stigma-related factors that are relevant to the experiences of individuals in diverse cultural contexts. To implement effective anti-stigma programmes it is vital to identify and prioritize WMM for primary healthcare providers and people with lived experience of mental health conditions (PWLE). Our current objective was to explore WMM to primary healthcare providers, PWLE, primary care managers, and policymakers in Lebanon to inform mental health stigma reduction initiatives. Methods We conducted a total of 45 qualitative interviews with primary healthcare providers, PWLE, primary care managers, and policymakers. The WMM framework was applied to analyse data from primary healthcare centres in Lebanon to identify themes related to stigma against PWLE. The analysis identified common themes related to WMM. The analysis aimed to identify (a) WMM values for participants, (b) factors that threaten these WMM values and their relationship to stigma, and (c) potential interventions that could leverage WMM principles to reduce stigma. Results WMM for primary healthcare providers encompassed competency, time management, willingness, and self-care. WMM for PWLE focused on equality, support, compassion, and confidentiality. Policymakers emphasised resource sustainability as a top priority. Myths about mental health illnesses perpetuated threats to WMM, and organisational barriers also threatened WMM for primary healthcare providers and PWLE, thus creating major roadblocks to achieving stigma reduction. Conclusion This study identified key domains to understand the factors for WMM in reducing mental health stigma in Lebanon and explored factors that shape the values and priorities of both PWLE and primary healthcare providers. The study suggests assessing the effectiveness of anti-stigma interventions that actively engage PWLE in their design and implementation, while exploring the broader applicability of the WMM framework across different cultural and healthcare settings.